Economic Dynamics of Kolaka Regency Based on Gross Regional Domestic Product (GRDP) and Economic Growth Rate from 2021 to 2023 - Asrip Putera; Milyan Milyan; Misnawati Misnawati; Rince Tambunan (Journal of Law, Social Science and Management, 2025)
Background: Economic growth is an important indicator in evaluating regional development performance, including in Kolaka Regency, which holds significant potential in the mining and industrial processing sectors. Objective: This study aims to analyze the dynamics of economic growth in Kolaka Regency during the 2021–2023 period, based on Gross Regional Domestic Product (GRDP) data at both current and constant prices, as well as GRDP per capita. Method: A quantitative-descriptive approach was used to assess the economic growth rate, identify dominant sectors, and understand trends in public welfare improvement. Data were sourced from official publications of the Central Statistics Agency of Kolaka Regency and Southeast Sulawesi Province, and analyzed using time series methods and sectoral contribution analysis. Results: The study reveals a significant improvement in GRDP at current prices, increasing from IDR 24.69 trillion in 2021 to IDR 31.95 trillion in 2023, with the industrial processing and mining sectors as the main contributors. GRDP per capita rose from IDR 63.47 million to IDR 79.34 million over the same period, reflecting an improvement in public economic welfare. Conclusion: The study concludes that the economic growth in Kolaka Regency exhibits a positive trend, driven by key sectors. However, this growth must be supported by balanced development across all sectors to ensure equitable progress. Keywords: Economic Growth, GRDP, Per Capita, Kolaka, Key Sectors, Trend Analysis